Կրտսեր դպրոցականի անձի հոգեբանական առանձնահատկությունների ձևավորման գործում ընտանեկան կրթական միջավայրի ներքին կառուցվածքի ազդեցության գործոնային վերլուծություն - Հակոբյան, Նաիրա; Քոլյան, Աղավնի (Զանգակ հրատ.)
В статье представлен факторный анализ внутренней структуры комплиментарной среды семьи, на основе которого выделена типология обследованных младших школьников по содержательным социально– психологическим особенностям. The article summarizes the factorial analysis of inner structure of family cooperation environment on the basis of which typology of surveyed junior schoolchild is separated. As well as the social psychological characteristics of the above mentioned typology is given.
Keywords: Հոգեբանություն